Succession planning measures of Small and Medium Enterprise (SME) family businesses in Ghana - Ahmed, Yakubu Coffie (2016)
A thesis submitted to the Department of Managerial Science, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the degree of Master of Business Administration (Strategic Management and Consulting Option).